La lucha campesina por el agua :El caso de la junta administradora de agua potable y alcantarillado parroquia La Esperanza - Castillo Izurieta, Paulina Lizeth (2015)
The present work is an effort to reconstruct the process of struggle by the Administrative Board of Water Supply and Sewerage (Junta Administradora de Agua Potable y Alcantarillado-JAAP) of the Parish La Esperanza between 2005-2010, that was developed in a national context hightlighted by the neoliberalism, which drove specific state institutions and market to promote illegitimate mechanisms to coopt progressively the autonomy of water management in rural parishes in Ecuador, including the Parish La Esperanza. In this background, a group of people distinguished by promoting collective actions of resistance against to these mechanisms, and then had formed a new leadership of the JAAP that would be responsible for generating creative proposals and strategies, legal and legitimate ones -projects, alliances, partnerships with Non Governmental Organizations and Second Grade Organizations-, that initially let supporting the autonomous management of water, but gradually to establish a process of comprehensive development through water. This process of development included components of agroecological production and trade, sustainable management of native forests and moors, organizational-participatory reconfiguration of the JAAP with the inclusion of various parish actors to the organization, and the ongoing development of general assemblies, sectorized assemblies and community work (mingas); strengthening and renewaing of the social/community management of water, where the resource was not considered as a commodity, but as a vital component, a resource that is life and gives life. The systematization of this experience is a first step that looks for contributing to the historical memory, and to the strengthening and organizational renewaing of the JAAP.